2014
DOI: 10.2527/jas.2014-8202
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations of intramuscular fat content and fatty acid composition among muscles and with subcutaneous fat in Duroc pigs1

Abstract: There is an increasing interest in including intramuscular fat (IMF) content and fatty acid composition, particularly oleic acid (C18:1) content, in the selection objectives of pig lines for quality pork markets. These traits are costly and can be measured in more than 1 location, so knowing their correlation structure across muscles and with subcutaneous fat (SF) is necessary for developing optimum sampling and recording schemes. We analyzed the genetic and phenotypic correlations of IMF content and compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
9
22
0
Order By: Relevance
“…This mean value was in line with the mean heritability (0.25) reported for Iberian pigs by Fernández et al (2003). This value was lower than the values previously reported for heavy Duroc pigs (Suzuki et al, 2005;Ros-Freixedes et al, 2014) and for Landrace and for lean Large White pigs (Knapp et al, 1997;Hermesch et al, 2000). However, this estimate is in the rank of estimates (from 0.26 to 0.86) reported by Sellier (1998) from 19 different studies in "white" pigs.…”
Section: Genetic and Common Environment Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…This mean value was in line with the mean heritability (0.25) reported for Iberian pigs by Fernández et al (2003). This value was lower than the values previously reported for heavy Duroc pigs (Suzuki et al, 2005;Ros-Freixedes et al, 2014) and for Landrace and for lean Large White pigs (Knapp et al, 1997;Hermesch et al, 2000). However, this estimate is in the rank of estimates (from 0.26 to 0.86) reported by Sellier (1998) from 19 different studies in "white" pigs.…”
Section: Genetic and Common Environment Parameterssupporting
confidence: 88%
“…The posterior mean of the genetic additive correlation between BFT and IMF was moderately positive (0.31) with a probability of being greater than 0 of 0.72. This mean value was within the range of the estimates reported for Duroc pigs (Suzuki et al, 2005;Ros-Freixedes et al, 2014). This would seem to indicate that part of the BFT and IMF genetic control is independent.…”
Section: Genetic and Common Environment Parameterssupporting
confidence: 86%
“…It is the most abundant adipose tissue and for decades it has been selected against to improve the production efficiency of pork. Intramuscular fat content is also influenced by genetic type, ranging from 1.2%–2.7% in Pietrain pigs [5] to 2.7%–4.8% in Duroc pigs [6], although even within breed much wider ranges have been described [7]. IMF is the least abundant adipose tissue in the pig carcass and it has a favorable impact on meat quality, having optimal values around 1.5%–3% in fresh meat [8].…”
Section: Relationship Between Imf and Other Fat Depots In Pigsmentioning
confidence: 99%
“…Intramuscular fat (IMF) is one of the most important factors that affect meat quality (Fanatico et al, 2007;Ros-Freixedes et al, 2014;Li et al, 2019). Previous researches have indicated that IMF improved the quality of meat by improving the flavor, juiciness and tenderness (Gao and Zhao, 2009).…”
Section: Introductionmentioning
confidence: 99%